The Impact of Adopting E-Commerce Payments on E-Commerce Performance - Ha, Van Duong; Nguyen, Thi Thuy (Journal of Posthumanism, 2025)
An electronic payment gateway is a type of service that provides technical infrastructure to connect banks and payment acceptance units. Through electronic payment gateways, electronic payment or E-commerce payment is an important online payment model in business that allows businesses to sell online, providing online services to use payment gateways to receive money for goods and services from customers. E-commerce payments help these businesses attract customers and create easy, safe and convenient payment transactions through Internet-connected wireless devices such as tablets and phones. The purpose of this study is to determine the impact of E-commerce payments (ECPs) adoption by retailers in Vietnam on electronic commerce (E-commerce) performance through the application of the integrated model of The Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) and The Information Systems Success (IS success). Data collected from 816 retailers were analyzed through structural equation modeling. The research results show that ECPs providers, managers, retailers and stakeholders need to pay attention to and enhance Effort Expectancy, Social Influence, Facilitation Conditions, Hedonic Motivation, Habits, and Human Resources to enhance behavioral intention to use ECPs. At the same time, retailers increase Facilitation Conditions, Behavior intention to promote ECPs usage behavior. From promoting usage behavior, bringing satisfaction when using ECPs to increase M-Commerce Performance. These research findings have some important implications for the application of the UTAUT2 and IS Success integrated models, as well as practical applications to identify factors influencing and contributing to increased M-Commerce performance of retailers in Vietnam.